Beyond Java-Centric Growth: Analyzing Structural Change and Its Impact on Regional Income Convergence in Post-Decentralization Indonesia - Amrani, Amrani (International Journal of Economics (IJEC), 2026)
This study examines the relationship between structural change and regional income convergence in Indonesia following the 2001 fiscal decentralization. Utilizing quantitative analysis on 30 provinces over 2005–2018 and 514 districts from 2000–2017, we employ shift-share decomposition, club convergence testing (Phillips & Sul methodology), and dynamic panel data models. Results reveal that while Java Island maintains 57% of national GDP, post-decentralization patterns show heterogeneous convergence dynamics characterized by five distinct convergence clubs rather than uniform income convergence. Structural change, particularly within-sector productivity improvements, positively impacts regional growth, though effectiveness has declined. Dynamic structural effects increasingly negative, indicating labor reallocation toward less productive sectors. Despite decentralization policies, regional inequality persists, modulated by development thresholds and natural resource endowments. Policy implications suggest necessity for differentiated regional development strategies acknowledging structural heterogeneity across convergence clubs